2021
DOI: 10.3329/taj.v34i1.54914
|View full text |Cite
|
Sign up to set email alerts
|

Role of HRCT Scan of Chest in the Evaluation of COVID-19 Pneumonia

Abstract: Coronavirus disease (COVID-19) pneumonia emerged in Wuhan, China, in December 2019. It is a highly contagious viral disease spreading worldwide, with a rapid increase in the number of cases & deaths. COVID-19 pneumonia is characterized by fever, fatigue, dry cough, and dyspnea with other systemic features such as diarrhea, altered sensorium, stroke & multi-organ failure. HRCT chest is one of the most sensitive modalities for early detection of COVID-19 pneumonia & monitor the outcome of these patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, it is of paramount importance to identify more accurate prognostic biomarkers for the disease's prognosis.󠄀 The potential areas where COVID-19 biomarkers can be instrumental include [3]; 1) Early symptom severity and disease suspicion 2) Clear evidence and categorization of disease severity 3) Framing criteria for hospital admission 4) Identifying a cohort at high risk 5) Defining ICU admission standards 6) Therapy rationalization 7) A therapeutic response's evaluation 8) Prediction of outcome 9) Defining the criteria for ICU and/or hospital High-Resolution Computed Tomography (HRCT) examinations are another method to detect viral infections in the body. They can also assess the severity of pulmonary disease and the presence of sequelae, track the disease's course, and eliminate other possible diagnoses [4]. Numerous studies have reported a correlation between inflammatory lab markers, hospital stay, and oxygen requirements with CT severity scores in COVID-19 patients [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of paramount importance to identify more accurate prognostic biomarkers for the disease's prognosis.󠄀 The potential areas where COVID-19 biomarkers can be instrumental include [3]; 1) Early symptom severity and disease suspicion 2) Clear evidence and categorization of disease severity 3) Framing criteria for hospital admission 4) Identifying a cohort at high risk 5) Defining ICU admission standards 6) Therapy rationalization 7) A therapeutic response's evaluation 8) Prediction of outcome 9) Defining the criteria for ICU and/or hospital High-Resolution Computed Tomography (HRCT) examinations are another method to detect viral infections in the body. They can also assess the severity of pulmonary disease and the presence of sequelae, track the disease's course, and eliminate other possible diagnoses [4]. Numerous studies have reported a correlation between inflammatory lab markers, hospital stay, and oxygen requirements with CT severity scores in COVID-19 patients [5].…”
Section: Introductionmentioning
confidence: 99%